Performing Cultural Art, Preventing Femicide: Gender Interpretation of Reog Cemandi Dance Sidoarjo - Tsabitah Zain Mumtaz; Sony Sukmawan (Universitas Muhammadiyah Malang, 2024)
There are thousands of types of culture in the form of traditional arts that are diverse and still survive in the community. One example is the art of Reog Cemandi in Sidoarjo Regency. Its development, which until now has been able to be useful with a number of gender contents, makes it interesting to study. Various types of tools in the form of clothing, movements, poems, and offerings have gender meanings that are implemented in the lives of the surrounding community. This research aims to reveal the form and meaning of Reog Cemandi with gender concepts. At the same time, it examines the potential efforts to prevent femicide reflected in Reog Cemandi through socialist feminism. The data collection used interview, observation and documentation techniques. The data analysis was carried out through several stages, namely data reduction, data presentation and conclusions. To strengthen the research relationship, femicide prevention indicators were used as data analysis instruments.The results of this research show that Reog Cemandi gives an implicit message in the clothes, movements, poems, and offerings in it. The message has a strong gender meaning including gender insight, gender equality, and women's empowerment. The message has been implemented in the social life of the Cemandi community. This article provides an understanding of the gender meaning in Reog Cemandi which is implemented in community behavior so that it has the potential as an effort to prevent femicide. Terdapat ribuan jenis kebudayaan berwujud kesenian tradisional yang beragam dan masih bertahan di tengah masyarakat. Salah satu contohnya adalah kesenian Reog Cemandi Kabupaten Sidoarjo. Perkembangannya yang hingga kini mampu bermanfaat dengan sejumlah muatan gender membuatnya menarik untuk diteliti. Berbagai jenis piranti berupa busana, gerak, syair, dan sesaji didalamnya memiliki makna gender yang terimplementasikan dalam kehidupan masyarakat sekitar. Penelitian ini bertujuan untuk mengungkap bentuk dan makna Tari Cemandi yang berkonsep gender. Sekaligus menelaah potensi usaha pencegahan femisida yang tercermin dalam Reog Cemandi melalui feminis sosialis. Pengumpulan data penelitian menggunakan teknik wawancara, observasi dan dokumentasi. Adapun analisis data dilakukan melalui beberapa tahapan, yaitu reduksi data, penyajian data dan kesimpulan. Untuk memperkuat relasi penelitian, digunakan indikator pencegahan femisida sebagai instrumen analisis data. Hasil penelitian ini menunjukkan bahwa Reog Cemandi memberi pesan tersirat dalam topeng, busana, gerak, syair, dan sesaji di dalamnya. Pesan tersebut memiliki makna gender yang cukup kuat meliputi wawasan gender, kesetaraan gender, dan pemberdayaan perempuan. Pesan tersebut telah diimplementasikan dalam kehidupan sosial masyarakat Cemandi dengan perilaku-perilaku yang mendukung kesetaraan gender. Artikel ini memberi pemahaman mengenai makna gender dalam Tari Reog Cemandi yang terimplementasikan dalam perilaku masyarakat sehingga berpotensi sebagai upaya pencegahan femisida.